2020
DOI: 10.1039/d0sc04359a
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nanocrystal-dynamic porous polymer assemblies with effective energy transfer for sensitive diagnosis of urine copper

Abstract: Despite the remarkable mechanical/optical/electrical properties, the inorganic particles and dynamic polymer assemblies encountered the difficulties in compatibility with structural order and complexity. Here, covalent organic frameworks (COFs) constructed through reversible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…The high-resolution C 1s spectrum of OCNP@M7 exhibits four main peaks (Figure E), and the emerging one at 287.4 eV confirms the presence of the unique NCN structure from OCNP. The N 1s spectrum peak of OCNP@M7 (Figure F) can be deconvoluted into three components, which can be ascribed to the C–N–H band at 400.3 eV, the N–(C) 3 band at 399.5 eV, and the CNC at 398.9 eV, respectively. , Compared with those of pure M7, both the C–N–H and CNC peaks from OCNP@M7 were negatively shifted, presumably due to the intermolecular interactions between the functional groups (e.g., −OH) of OCNP and the Lewis basic triazole −N sites on the MAF-7 framework . As can be seen from thermogravimetric analysis (TGA) profiles in Figure S9, OCNP in the composite is more thermally stable than pure OCNP, possibly because of the multiple noncovalent interactions between MAF-7 and OCNP.…”
Section: Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The high-resolution C 1s spectrum of OCNP@M7 exhibits four main peaks (Figure E), and the emerging one at 287.4 eV confirms the presence of the unique NCN structure from OCNP. The N 1s spectrum peak of OCNP@M7 (Figure F) can be deconvoluted into three components, which can be ascribed to the C–N–H band at 400.3 eV, the N–(C) 3 band at 399.5 eV, and the CNC at 398.9 eV, respectively. , Compared with those of pure M7, both the C–N–H and CNC peaks from OCNP@M7 were negatively shifted, presumably due to the intermolecular interactions between the functional groups (e.g., −OH) of OCNP and the Lewis basic triazole −N sites on the MAF-7 framework . As can be seen from thermogravimetric analysis (TGA) profiles in Figure S9, OCNP in the composite is more thermally stable than pure OCNP, possibly because of the multiple noncovalent interactions between MAF-7 and OCNP.…”
Section: Results and Discussionmentioning
confidence: 64%
“…22,23 Compared with those of pure M7, both the C−N−H and CNC peaks from OCNP@M7 were negatively shifted, presumably due to the intermolecular interactions between the functional groups (e.g., −OH) of OCNP and the Lewis basic triazole −N sites on the MAF-7 framework. 24 As can be seen from thermogravimetric analysis (TGA) profiles in Figure S9, OCNP in the composite is more thermally stable than pure OCNP, possibly because of the multiple noncovalent interactions between MAF-7 and OCNP. The significant differences between the TGA profiles confirm that OCNP was successfully incorporated in the MAF-7 skeleton in the OCNP@M7 composite.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The quenching-based assay here designed was finally compared to the recently developed fluorescence-based methods for Cu 2+ detection in urine [ 8 , 9 , 10 , 11 ] ( Table S4 ), i.e., carbon dots (CDs) combined with covalent organic frameworks (COFs), chitosan/L-histidine-stabilized silicon nanoparticles (CS/L-His–SiNPs), nitrogen-doped quantum carbon dots (ND-CQDs), and blue CDs (bCDs) combined with green quantum dots (gQDs). These methods offer better LODs values [ 8 , 9 ] (except in Li et al and Zhang et al, in which the LOD values were not calculated for human urine samples [ 10 , 11 ]). However, these nanostructures require long and laborious synthetic procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that an accumulation of Cu 2+ affects the activity of dopaminergic neurotransmitters, potentially leading to neurodegenerative disorders and mental issues, including anxiety, depression, language, and cognitive impairment [ 5 , 6 , 7 ]. In this context, a few fluorescent methods were developed for Cu 2+ quantitative analysis in urine [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In this study, for the first time, the fluorescent properties of a novel fluorophore derived from serotonin (SE) self-oxidation and polymerization were exploited for sensitive Cu 2+ detection in human urine without matrix pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Selective detection of Fe 3+ ions against other interfering ions including Ag + , Co 2+ , Ni 2+ , Al 3+ et al. is necessary for practical application in the human body [37] . 2 mg PAF powder (LNU‐22 or LNU‐24) was dispersed in 5 mL THF solvent after that 1 mL nitrate solution with a concentration of 0.01 mol L −1 was poured into the mixture.…”
Section: Resultsmentioning
confidence: 99%